HDAC Family members intertwined in the regulation of autophagy: a druggable vulnerability in aggressive tumor entities - Koeneke, Emily; Witt, Olaf; Oehme, Ina (Cells, 2015)
The exploitation of autophagy by some cancer entities to support survival and dodge death has been well-described. Though its role as a constitutive process is important in normal, healthy cells, in the milieu of malignantly transformed and highly proliferative cells, autophagy is critical for escaping metabolic and genetic stressors. In recent years, the importance of histone deacetylases (HDACs) in cancer biology has been heavily investigated, and the enzyme family has been shown to play a role in autophagy, too. HDAC inhibitors (HDACi) are being integrated into cancer therapy and clinical trials are ongoing. The effect of HDACi on autophagy and, conversely, the effect of autophagy on HDACi efficacy are currently under investigation. With the development of HDACi that are able to selectively target individual HDAC isozymes, there is great potential for specific therapy that has more well-defined effects on cancer biology and also minimizes toxicity. Here, the role of autophagy in the context of cancer and the interplay of this process with HDACs will be summarized. Identification of key HDAC isozymes involved in autophagy and the ability to target specific isozymes yields the potential to cripple and ultimately eliminate malignant cells depending on autophagy as a survival mechanism.
Gesehen am 14.07.2020